Embedded controller hardware design. - Arnold, Ken (Embedded technology series)
Embedded Controller Hardware Design is THE definitive guide to designing reliable microcontrolelr hardware for real-world applications. It is a thorough introduction to embedded hardware design that stresses designing for reliability in "real world" applications. The book provides a comprehensive overview of microcontroller architecture, design analysis, memory technologies, handling interrupts, techniques for hardware interfacing, designing for reliability, and handling issues found in real-world applications. The author discusses hardware and software design in an integrated fashio.